2005
DOI: 10.1002/jbt.20050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacoside A on membrane‐bound ATPases in the brain of rats exposed to cigarette smoke

Abstract: Membrane-bound enzymes play a vital role in neuronal function through maintenance of membrane potential and impulse propagation. We have evaluated the harmful effects of chronic cigarette smoking on membrane-bound ATPases and the protective effect of Bacoside A in rat brain. Adult male albino rats were exposed to cigarette smoke for a period of 12 weeks and simultaneously administered with Bacoside A (the active principle isolated from Bacopa monniera) at a dosage of 10 mg/kg b.w/day, p.o. The levels of lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 48 publications
(54 reference statements)
6
32
0
Order By: Relevance
“…In this study Na + /K + -ATPase activity was diminished while Na + level was elevated and K + concentration was lowered in the brain of cigarette smoke exposed rats. These results are consistent with earlier reports (Anbarasi et al 2005a;Jaques et al 2013). Besides, Tulenko et al (1988) also have shown decrease of Na + /K + -ATPase activity and increase of Na + level in arterial cell wall by exposure to cigarette smoke, which was attributed to the reorganization of lipid bilayer by increased TC/PL ratio.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…In this study Na + /K + -ATPase activity was diminished while Na + level was elevated and K + concentration was lowered in the brain of cigarette smoke exposed rats. These results are consistent with earlier reports (Anbarasi et al 2005a;Jaques et al 2013). Besides, Tulenko et al (1988) also have shown decrease of Na + /K + -ATPase activity and increase of Na + level in arterial cell wall by exposure to cigarette smoke, which was attributed to the reorganization of lipid bilayer by increased TC/PL ratio.…”
Section: Discussionsupporting
confidence: 95%
“…In this study, we observed low Ca 2+ -ATPase activity and high Ca 2+ concentration in the brain of rats exposed to cigarette smoke. These results are concomitant with previous studies (Anbarasi et al 2005a;Jaques et al 2013). Calcium invasion followed by cigarette smoke exposure suppressed Ca 2+ -ATPase activity in the rat brain.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In vivo chronic exposure of rat brain tissue to cigarette smoke significantly decreases membrane-bound ATPases, which alters ion homeostasis, and leads to increased Ca2+ and Na+ levels in the cytosol of various cell types 87 , as well as increase Ca2+ in mitochondria, which is associated with neuronal injury or death 88 . Increased mitochondrial Ca 2+ secondary to cigarette condensate exposure is associated with damage to the inner mitochondrial membrane (e.g., membrane swelling) and vacuolization of the matrix.…”
Section: Smoking Associated Cell Injury In Brainmentioning
confidence: 99%
“…Other saponins have also been reported, but their activities are relatively unexplored (Mahato et al, 2000). Moreover, the antioxidant (Anbarasi et al, 2005), anticancer (Elangovan et al, 1995), antiinflammatory (Jain et al, 1994) and superoxide inhibitor (Pawar et al, 2001) effects of the B. monniera extract relating to immunological activity have been investigated. The present study was undertaken to assess the possible immunomodulating activities of B. monniera extract and bacoside A in relation to its folklore use and other pharmacological activities as previously reported.…”
Section: Introductionmentioning
confidence: 97%